Effect of Reefs and Faults on Oil Reservoir Performance - Case Study: Carbonate Reservoir, Southern Iraq - Al-Rikaby, Alaa S.; Al-Jawad, Mohammed S. (Journal of Petroleum Research and Studies, 2025)
The study area is located in an unstable region within the Mesopotamian basin of the Arabian plate. It is surrounded by several oil fields that produce hydrocarbons from NW-SE-trending anticline formations, which are compatible with the direction of the Zagros folded axis. The study area is characterized by the presence of bubble point pressure discrepancy at the same productive reservoir unit, which raised several doubts about the faults or reefs that led to this phenomenon and the future impact on the development strategy of the study area. The study aimed to assess how faults and reef affect the development plan for carbonate oil reservoir. The process involves three steps tailored to fit the specific characteristics of the research area before the development strategy of oil production. The first step was creating a seismic model to identify any irregular amplitudes of reflected events and abrupt discontinuities, which could indicate either a reef or a fault. This was followed by creating a geological model based on faults and reef, developing a reservoir model, and conducting historical matching. The study proved the presence of a fault and excluded the presence of a reef. Four development plan scenarios were created for a 20-year period based on the probabilities of the fault and reef. The study found that case four had the most favorable results among all the cases. This case showed a production plateau that lasted for seven years with slight fluctuations.